Influence of environmental variability and Emiliania huxleyi ecotypes on alkenone-derived temperature reconstructions in the subantarctic Southern Ocean - Rigual-Hernández, A.S. (2022)
Long-chain unsaturated alkenones produced by haptophyte algae are widely used as paleotemperature indicators. The unsaturation relationship to temperature is linear at mid-latitudes, however, non-linear responses detected in subpolar regions of both hemispheres have suggested complicating factors in these environments. To assess the influence of biotic and abiotic factors in alkenone production and preservation in the Subantarctic Zone, alkenone fluxes were quantified in three vertically-moored sediment traps deployed at the SOTS observatory (140°E, 47°S) during a year. Alkenone fluxes were compared with coccolithophore assemblages, satellite measurements and surface-water properties obtained by sensors at SOTS. Alkenone-based temperature reconstructions generally mirrored the seasonal variations of SSTs, except for late winter when significant deviations were observed (3–10 °C). Annual flux-weighted averages in the 3800 m trap returned alkenone-derived temperatures ~1.5 °C warmer than those derived from the 1000 m trap, a distortion attributed to surface production and signal preservation during its transit through the water column. Notably, changes in the relative abundance of E. huxleyi var. huxleyi were positively correlated with temperature deviations between the alkenone-derived temperatures and in situ SSTs (r = 0.6 and 0.7 at 1000 and 2000 m, respectively), while E. huxleyi var. aurorae, displayed an opposite trend. Our results suggest that E. huxleyi var. aurorae produces a higher proportion of C37:3 relative to C37:2 compared to its counterparts. Therefore, the dom inance of var. aurorae south of the Subtropical Front could be at least partially responsible for the less accurate alkenone-based SST reconstructions in the Southern Ocean using global calibrations. However, the observed correla tions were largely influenced by the samples collected during winter, a period characterized by low particle fluxes and slow sinking rates. Thus, it is likely that other factors such as selective degradation of the most unsaturated alkenones could also account for the deviations of the alkenone paleothermometer.